2005
DOI: 10.1071/wr04094
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of survey methods for arboreal possums in jarrah forest, Western Australia

Abstract: Comparative trials of different survey methods were conducted in the southern jarrah (Eucalyptus marginata) forest to determine the most efficient means of detecting koomal (common brushtail possum, Trichosurus vulpecula hypoleucus) and ngwayir (western ringtail possum, Pseudocheirus occidentalis). In particular, we examined different trapping and spotlighting methods and compared these with scat surveys. Six different trapping methods (derived by combining three bait types and two trap positions) were compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 65 publications
1
13
0
2
Order By: Relevance
“…It is important to mention, however, that food baits can act as a source of variation in detection probability, as animals may be more likely to investigate food-based baits when they are hungry or depending on seasonal variations in food resources. Indeed the efficiency of baits in attracting a particular species has been shown to vary according to factors such as individual behavior and age, time of the year, and population size (Short et al 2002) Studies that include more than one species have also consistently shown that the efficiency of baits varies strongly among species (Andelt and Woolley 1996;Wayne et al 2005;Campbell and Long 2008). In our study, although the baits containing banana were consistently better than scent lures for five species, at least one species for which we had a large number of records-the nine-banded armadillo (Dasypus novemcinctus)-did not show preference for banana.…”
Section: Comparing Baitsmentioning
confidence: 98%
“…It is important to mention, however, that food baits can act as a source of variation in detection probability, as animals may be more likely to investigate food-based baits when they are hungry or depending on seasonal variations in food resources. Indeed the efficiency of baits in attracting a particular species has been shown to vary according to factors such as individual behavior and age, time of the year, and population size (Short et al 2002) Studies that include more than one species have also consistently shown that the efficiency of baits varies strongly among species (Andelt and Woolley 1996;Wayne et al 2005;Campbell and Long 2008). In our study, although the baits containing banana were consistently better than scent lures for five species, at least one species for which we had a large number of records-the nine-banded armadillo (Dasypus novemcinctus)-did not show preference for banana.…”
Section: Comparing Baitsmentioning
confidence: 98%
“…Runnel counts, track counts and faecal-pellet counts were undertaken at each site 10 days before trapping, to ensure that counts were not influenced by the presence of traps or bait (Wayne et al 2005). Eight transects, each 240 m long, were established as a part of the trapping web and were visited each morning for 10 consecutive days.…”
Section: Sign and Sighting Surveysmentioning
confidence: 99%
“…Indirect methods of surveying population size are often considered a more cost effective and practical alternative to mark-recapture studies, despite weaknesses documented in the literature relating to known biases, inconsistent detection and an inability to meet model assumptions (Nichols and Pollock 1983;Montgomery 1987;Slade and Blair 2000;McKelvey and Pearson 2001;Hopkins and Kennedy 2004). Indirect monitoring techniques such as the use of photographic captures (Karanth and Nichols 1998), driving transects (Caro 1999;Olson et al 2005), walked line transects (Short and Turner 1991;le Mar et al 2001;Poole et al 2003;Wayne et al 2005) and dung-pellet counts (Johnson and Jarman 1987;Allen et al 1996;Buckland et al 2001;Hayward et al 2003) have been widely used to provide a quantitative estimate of population size for small and mediumsized mammals. More recently, these have been coupled with sophisticated models that can actively account for changing detection probabilities (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…ou de monitoramento de espécies alvo (e.g. Wayne et al 2005), indicam que a eficiência das iscas varia muito a depender da espécie considerada.…”
Section: Comparação Entre As Iscasunclassified
“…Se por um lado alguns estudos demonstraram que estes índices são correlacionados com a densidade das espécies (e.g., Smallwood 1997, Stander 1998, Sargeant et al 2003, por outro, o uso deste método é prejudicado pela chuva, requer a verificação freqüente por um profissional treinado (Silveira et al 2003) A comparação e avaliação da eficiência de métodos de amostragem de mamíferos de maior porte foi realizada para poucas espécies e ambientes e sugere que o desempenho de cada método depende do comportamento das espécies alvo, das condições ambientais e das variáveis analisadas (Wilson e Delahay 2001, Gompper et al 2006. Dentre os estudos que comparam diferentes métodos de amostragem de mamíferos de maior porte, nenhum foi realizado em paisagens alteradas, a maioria foca no desempenho de métodos para uma ou poucas espécies (Bull et al 1992, Gros et al 1996, Foresman e Pearson 1998, BeckKing e von Helversen 1999, Sharp et al 2001, Harrison et al 2002, Harrison 2006), e poucos foram realizados em florestas tropicais (Gros et al 1996, Gaidet-Drapier et al 2006) ou neotropicais (Beck-King e von Helversen 1999, Silveira et al 2003 Short et al 2002, Pardini et al 2003, Wayne et al 2005, Giman et al 2007). Entre estes, apenas dois foram realizados nos neotrópicos (Pardini et al 2003 Fotografias seqüenciais da mesma espécie geradas pela mesma câmera foram consideradas registros independentes quando tiradas com pelo menos uma hora de intervalo (Fonseca et al 1996).…”
Section: Introductionunclassified